Comparative Study of State Jurisdiction: The Protection Towards Geographical Indication at Indonesia, the EU and US - Rianda Dirkareshza; Anni Alvionita Simanjuntak (Audito Comparative Law Journal (ACLJ), 2023)
Geographical Indication (GI) is one of the Intellectual Property Rights features. In this instance, one component that needs to be highlighted is its registration. Unfortunately, there are several infringements of Indonesian GI exist, such as Indonesian product registration being claimed by foreigners or outsiders. This article examines the legal protection of Geographical Indications based on Indonesian Legal Instruments and the law of outsiders parties and the international’s rule in Geographical Indication dispute settlement among countries. This article uses normative juridical research methods with a descriptive-analytical approach using national and international laws and relevant regulations to its issues. The findings revealed that protecting Geographical Indications in the International domain often causes polemics due to the need for firmness regarding the International Agreements’ substance. The arrangement of Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPs) merely requires legal provisions for each country in protecting Geographical Indications. Consequently, each country has fundamental different legal for protecting GI, and the legal uncertainty in International Agreement raises new issues.